The Teachers’ Roles in Reducing the Interference of L1 in Audio-lingual Classrooms: A Qualitative Case Study in Malaysian Primary School - Rahim, Mohammad Naim; Ahmadi, Sayed Ali Reza (REiLA : Journal of Research and Innovation in Language, 2021)
This research article explores the teachers’ roles in reducing L1 (First Language) interference in audio-lingual classrooms. The main concern of the audio-lingual method is to focus less on grammar and teaching it inductively. There is also an emphasis on pronunciation in this method. Using tapes, visual language aids, and new materials are presented in an interactive model. The teacher presents a new structure using communicative models, and there is less focus on L1. The study applies a qualitative case study and uses observation and interview data collection techniques in a particular primary school of Malaysia during the English language sessions. The thematic analysis technique is performed to categorize the significant findings into three main themes: teacher as a role model, teacher as an orchestra leader, and teacher as a motivator. The data from classroom observation is triangulated to determine how the data is closed to the interview. The finding shows the problematisation of using L1 in teaching L2 (Second Language) since the interference of L1 negatively impacts learning L2. The study contributes to the perspective that English teachers in audio-lingual classrooms are expected to understand their objective roles. The result also implies the teachers' significance to accept that using L1 in maxim spoils learning L2, especially in an audio-lingual classroom.